Stress parental, adaptation socio-émotionnelle et rendement scolaire des frères et soeurs d’enfants autistes: Parental stress, social-emotional adjustment, and academic performance of siblings of children with autism - Gascon, Hubert; Verreault, Roxane (Revue francophone de la déficience intellectuelle, 2015)
L'intérêt des milieux de pratique et de recherche à l'égard du vécu des frères et des soeurs des personnes handicapées est très récent. Pourtant, quelques études observent que les familles dont un enfant présente des incapacités vivent un stress plu élevé que les familles dont les enfants n'ont pas d'incapacité (Dyson, 1993; Dyson et Fewell, 1986; Fuller et Rankin, 2994). Et, les parents d'enfants autistes vivent un plus grand stress que les parents d'enfants présentant une trisomie ou ayant une autre déficience intellectuelle (Holroyd et McArtur, 1976; Donovan, 1988; Morin, 2003). L'objectif visé par le projet est de mieux comprendre la situation des frères et des soeurs d'âge scolaire d'enfants autistes par rapport à leur réseau de soutien social, leur adaptation socio-émotionnelle et leur Abstract The interest of the practice and research communities in the experiences of siblings of people with disabilities is very recent. However, a few studies have found that families with children with disabilities experience more stress than families with children without disabilities (Dyson, 1993; Dyson & Fewell, 1986; Fuller & Rankin, 2994). And, parents of children with autism experience greater stress than parents of children with Down syndrome or other intellectual disabilities (Holroyd & McArtur, 1976; Donovan, 1988; Morin, 2003). The goal of this project is to better understand the situation of school-aged siblings of children with autism in relation to their social support network, social-emotional adjustment, and academic performance, and the relationships of these variables to each other. Also, the relationships between these variables and the stress experienced by their parents are examined.